2020
DOI: 10.1016/j.gene.2019.144132
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NF-κB signaling pathway in the pathogenesis of colorectal cancer

Abstract: The NF-κB signaling pathway is a key regulator of CRC cell proliferation, apoptosis, angiogenesis, inflammation, metastasis, and drug resistance. Over-activation of the NF-κB pathway is a feature of colorectal cancer (CRC). While new combinatorial treatments have improved overall patient outcome; quality of life, cost of care, and patient survival rate have seen little improvement. Suppression of the NF-κB signaling pathway using biological or specific pharmacological inhibitors is a potential therapeutic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 78 publications
(43 reference statements)
4
122
0
Order By: Relevance
“…In our study, we revealed that elevated expression of G9a suppressed IκBαprotein and increased NF-κB luciferase activity, activating FAK signaling and promoting migration and invasion in NSCLCs. Similarly, recent study has demonstrated that NF-κB signaling pathway playsa very important role in oncogenesis and metastasis [47].NF-κBsignaling pathway has previously been shown to be associated with FAK activation and increased cell proliferation in lung cancer [48]. Tetraspanin 15 (TSPAN15) promoted esophageal cancer metastasis via activating NF-κB through regulating IκBαphosphorylation [49].In NSCLC, researchers have found that HMGB1mediated cancer cell motility is mediated in part by NF-κB-activated FAK signaling pathway [50].These and other studies demonstrate the importantrole of NF-κB in FAK signaling pathway and cancer metastasis and suggest thatNF-κB can also be considered as a potential druggable target in patients with G9a overexpressing lung cancers.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we revealed that elevated expression of G9a suppressed IκBαprotein and increased NF-κB luciferase activity, activating FAK signaling and promoting migration and invasion in NSCLCs. Similarly, recent study has demonstrated that NF-κB signaling pathway playsa very important role in oncogenesis and metastasis [47].NF-κBsignaling pathway has previously been shown to be associated with FAK activation and increased cell proliferation in lung cancer [48]. Tetraspanin 15 (TSPAN15) promoted esophageal cancer metastasis via activating NF-κB through regulating IκBαphosphorylation [49].In NSCLC, researchers have found that HMGB1mediated cancer cell motility is mediated in part by NF-κB-activated FAK signaling pathway [50].These and other studies demonstrate the importantrole of NF-κB in FAK signaling pathway and cancer metastasis and suggest thatNF-κB can also be considered as a potential druggable target in patients with G9a overexpressing lung cancers.…”
Section: Discussionmentioning
confidence: 93%
“…During the genesis and development of tumor, IKKβ phosphorylation increases, and further induces phosphorylation and ubiquitination of IκBα, which leads to the NF‐κB phosphorylation and separates from the complex of NF‐κB/IκBs. The free NF‐κB moves into the nucleus though the nuclear membrane and binds to its specific DNA sequence that induces high expression of the cell survival and antiapoptosis target genes of its downstream, and reduces the sensitivity of tumor cells to radiotherapy (DiDonato, Mercurio, & Karin, 2012; Mulero, Huxford, & Ghosh, 2019; Soleimani et al., 2019). Therefore, the inhibition of NF‐κB signaling pathway could enhance the radiosensitivity of tumor.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies found that NF-κB signaling pathway plays highly important roles in cell proliferation, apoptosis, angiogenesis, in ammation, metastasis, and drug resistance. [23][24][25] A variety of stimuli coalesce on NF-κB activation, which can in turn mediate varied transcriptional programs. 26 In this study, the protein expression of P65, IκBα, and their phosphorylated were detected by western blot.…”
Section: Discussionmentioning
confidence: 99%